The evolving burden of drug use disorders: a comprehensive epidemiological analysis from the 2021 Global Burden of Disease study - Liu, Yujuan; Zhang, Ning; Ren, Weifang; Lv, Xiaoqun; Ran, Shan; Tan, Xiaofang; Zhao, Qiongyue (Frontiers in Psychiatry, 2025)
BackgroundDrug use disorders (DUDs) pose a substantial global health burden, yet comprehensive analyses of their epidemiological trends, sociodemographic drivers, and cross-national disparities remain limited. Leveraging data from the Global Burden of Disease (GBD) 2021 study, we evaluated the global, regional, and national burden of DUDs from 1990 to 2021, focusing on opioids, cannabis, cocaine, amphetamines, and other substances.MethodsUsing GBD 2021 data, we analyzed age-standardized incidence, prevalence, mortality, and disability-adjusted life years (DALYs) for DUDs across 204 countries. Bayesian meta-regression (DisMod-MR 2.1) and age-period-cohort modeling were applied to quantify trends, stratified by sex, age, region, and socio-demographic Index (SDI). Uncertainty intervals (UIs) were derived from 1,000 posterior draws.ResultsGlobally, incident DUD cases increased by 36% (95% UI: 31%–40%) from 1990 to 2021, while mortality more than doubled (122%, 95% UI: 100%–149%). Despite an 8% decline in age-standardized incidence rates (184.31 to 169.39 per 100,000), mortality rates rose by 31% (1.26 to 1.65 per 100,000), and DALYs increased by 15% (166.44 to 190.97 per 100,000). High-income North America experienced an 11.2-fold surge in mortality (6,125 to 74,451 deaths), contrasting with East Asia’s 15% reduction in incident cases. Opioid-related DALYs rose by 32% (103.69 to 137.15 per 100,000), driven by high-SDI regions, while cocaine-related mortality doubled (108%, 0.07 to 0.15 per 100,000). Males aged 20–24 had 1.35-fold higher incidence than females (386.01 vs. 285.59 per 100,000), with mortality peaking at ages 25–29 (3.45 vs. 1.12 per 100,000). SDI exhibited a strong positive correlation with DALYs (Spearman ρ=0.70, *p*<0.01), though amphetamine use disorders peaked at moderate SDI levels (0.6–0.8).ConclusionThe escalating mortality and DALYs despite declining incidence highlight systemic gaps in harm reduction and treatment access, particularly in high-SDI nations. Opioid and cocaine crises demand urgent regulatory reforms and integrated care models. Global disparities underscore the need for context-specific interventions addressing socioeconomic determinants, polysubstance use, and aging populations. Policymakers must prioritize data-driven strategies aligned with SDG 3 targets (good health and well-being) to mitigate the growing burden of DUDs.